Gestão de resíduo e tecnologia ambiental na fabricação de tijolos solo-cimento - Samson, Bárbara Pereira (2016)
Currently we have been sought new constructive solutions involving environmental sustainability through the reduction / elimination of waste of raw materials and final products. The reduction of waste has been granted by the rational use of materials and various forms of reuse, for both are studied and developed technologies capable of absorbing this waste. Under the basic sanitation is highlighted waste generated in water treatment plants during the process of purifying plants of water intended for human consumption. This residue is commonly called sludge. For environmental issues, frequent studies point to the incorporation of this waste in construction materials such as conventional bricks and soil cement. Laboratory analyzes were: Fluorescence Xray (XRF) , Chemical Oxygen Demand (COD) , Biochemical Oxygen Demand (BOD), Particle size , Plasticity Index and resistance to simple compression. This the following study aims to evaluate the incorporation of the waste generated in the Water Treatment Plant - Gramame in soil-cement bricks type. The concreteness of research leads to consideration of the incorporation of the waste generated in the Water Treatment Plant - Gramame in low percentages do not affect the strength of soil-cement bricks. This result associated with a considerable concentration of Organic matter.